Alternatif Untuk Meminimalisasi terhadap Pelanggaran HAM dalam Penegakan Hukum Pidana - Ryan Aditama (Wajah Hukum, 2020)
Related to the general provisions of Law No. 39 of 1999 concerning Human Rights, which states that the beginnings of the history of the Indonesian nation to date have recorded various problems including: suffering, misery and social inequality, resulting from unjust and discriminatory acts and actions on ethnic, racial, cultural understanding, language, color, skin, and religion, as well as class, gender, and even social status and others. These unjust and discriminatory acts are included in violations of human rights, both vertically "carried out by the state apparatus itself to citizens or even vice versa" or those that are horizontal "ie between citizens themselves" and do not allow those included in the category for gross violations of the conception of human rights (grossviolation of human rights). This alternative to minimize human rights violations in criminal law enforcement is an effective way to reduce the number of human rights violations in Indonesia.